2016
DOI: 10.1002/ppap.201600157
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric‐pressure nonthermal plasma synthesis of ammonia over ruthenium catalysts

Abstract: Atmospheric‐pressure nonthermal plasma was used to synthesize ammonia from nitrogen and hydrogen over ruthenium catalysts. Formation of NH3 in a N2‐H2 mixture altered the plasma characteristics due to the low ionization potential of NH3 (10.15 eV). The optimum gas ratio was found at N2:H2 = 4:1 by volume (i.e., N2‐rich conditions). When plasma was operated at a temperature below 250 °C, the NH3 concentration increased linearly with increasing specific input energy (SIE). For the Ru(2)‐Mg(5)/γ‐Al2O3 catalyst at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
224
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(242 citation statements)
references
References 38 publications
(35 reference statements)
14
224
1
Order By: Relevance
“…They suggested that the enhancement by the ferroelectric material is attributed to two main reasons: (1) effect on the discharge behavior, which resulted in a higher electron density, and (2) the catalytic effect of the ferroelectric material surface. Due to the good performance in conventional ammonia synthesis process, Ru based catalysts have been selected as the reference n plasma-assisted process [101,115,121,150]. However, the ionization energy of Ru is 7.36 eV, and it might be difficult to be ionized by atmospheric DBD plasma.…”
Section: Catalysts Selectionmentioning
confidence: 99%
“…They suggested that the enhancement by the ferroelectric material is attributed to two main reasons: (1) effect on the discharge behavior, which resulted in a higher electron density, and (2) the catalytic effect of the ferroelectric material surface. Due to the good performance in conventional ammonia synthesis process, Ru based catalysts have been selected as the reference n plasma-assisted process [101,115,121,150]. However, the ionization energy of Ru is 7.36 eV, and it might be difficult to be ionized by atmospheric DBD plasma.…”
Section: Catalysts Selectionmentioning
confidence: 99%
“…There has been some work carried out on ammonia synthesis using plasma catalysis. [16][17][18] Over the years, energy yields have been as high as 35 g-NH 3 /kWh while using a pulsed AC atmospheric pressure dielectric barrier discharge (DBD) reactor, [19] showing the potential of small-scale production of ammonia using plasma-catalysis. Recently, Peng et al [20] employed a pulsed DBD reactor with MgCl 2 acting as catalyst and absorbent, leading to enhanced conversions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been several reports of ammonia synthesis using dielectric barrier discharge, microwave, glowing arc discharge, and radiofrequency (RF) plasma [9]. Among the most notable reports are Patil [13], all of them performed in a dielectric barrier discharge (DBD). These reports indicated the highest energy yield of ammonia in the range of 5-35 g-NH 3 /kWh.…”
Section: Introductionmentioning
confidence: 99%